2015
DOI: 10.1186/s13018-015-0311-8
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative evaluation of the impact of viable medial meniscus graft type on the biochemical and biomechanical properties of the rabbit tibial cartilage

Abstract: BackgroundKnowledge of the impact of viable medial meniscus allograft and autograft transplantation on biochemical and mechanical properties of cartilage is needed to understand the development of joint osteoarthritis. The purpose of this study was to evaluate this relationship 6 months after viable medial meniscal autograft and allograft transplantation.MethodsTwenty rabbits were chosen for the study. The medial menisci were excised from 14 animals and stored under tissue culture conditions for 2 weeks. Seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Without the rapid freezing process used to preserve fresh-frozen allografts, histocompatibility antigens remain intact, increasing the risk of immune response for both fresh and cryopreserved allografts. 27,70…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Without the rapid freezing process used to preserve fresh-frozen allografts, histocompatibility antigens remain intact, increasing the risk of immune response for both fresh and cryopreserved allografts. 27,70…”
Section: Resultsmentioning
confidence: 99%
“…Some investigators believe that these cells could help maintain the extracellular matrix and reduce the urgency of repopulation, whereas others question the benefit of viable cells given that in vivo studies have shown repopulation of the graft with host cells after 4 weeks. 3,27,46,50,70 There is a possibility that the remaining viable cells signal to the host cells to repopulate and repair the tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies on meniscal decellularization, tensile properties are mostly attributed to collagen fibers, while compressive properties are mostly associated with GAGs (Abdelgaied et al 2015 ; Maier et al 2007 ; Schmidt et al 1990 ; Zhu et al 1993 ). In addition, GAGs colocalized with type II collagen could maintain viscoelastic properties, compression stiffness and tissue hydration (Buma et al 2007 ), while a 1% decrease in GAG content could result in a 1.1% decrease in elasticity (Zwierzchowski et al 2015 ). Since meniscal biomechanical properties are closely related to the structure and organization of the collagen network and GAG content, the ECM retaining these components after decellularization would, at the same time, possess favorable biomechanical characteristics.…”
Section: Discussionmentioning
confidence: 99%